2005
DOI: 10.1021/ic050411m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligand Structure on the Pathways for Iron Release from Human Serum Transferrin

Abstract: Rate constants for the removal of iron from N-terminal monoferric transferrin have been measured for a series of phosphate and phosphonocarboxylic acids in pH 7.4 0.1 M hepes buffer at 25 degrees C. The bidentate ligands pyrophosphate and phosphonoacetic acid (PAA) show a combination of saturation and first-order kinetics with respect to the ligand concentration. Similar results are observed following a single substitution at the 2-position of PAA to give 2-benzyl-PAA and phosphonosuccinic acid. In contrast, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…According to these results, pyrophosphate can bind iron loaded on transferrin and deliver it to ferritin [26] . Other authors demonstrated transfer from iron-loaded transferrin to pyrophosphate [37] , [38] . The results described in these reports prompted us to check for the effect of pyrophosphate on the use of iron-loaded transferrin as an iron source.…”
Section: Resultsmentioning
confidence: 96%
“…According to these results, pyrophosphate can bind iron loaded on transferrin and deliver it to ferritin [26] . Other authors demonstrated transfer from iron-loaded transferrin to pyrophosphate [37] , [38] . The results described in these reports prompted us to check for the effect of pyrophosphate on the use of iron-loaded transferrin as an iron source.…”
Section: Resultsmentioning
confidence: 96%
“…These kinetic effects do not correlate well with simple changes in the ionic strength of the solutions [35]. Nor do they correlate well with the Hoffmeister series [53,54], which describes general anion affects on protein structure.…”
Section: Anion Effects On Iron Releasementioning
confidence: 90%
“…We have proposed that the first-order term represents a separate reaction pathway for iron removal that involves the replacement of the synergistic carbonate by the incoming ligand and is not subject to a rate-limiting protein conformational change [32,[35][36][37][38]. The disulfonates show very distinct effects on the saturation and linear components of iron release.…”
Section: Anion Effects On Iron Releasementioning
confidence: 99%
See 2 more Smart Citations